Holocene Environmental Dynamics of the Lago Cochrane/Pueyrredón Valley, Central West Patagonia (47°S) - Maldonado, Antonio; de Porras, María Eugenia; Martel-Cea, Alejandra; Reyes, Omar; Nuevo-Delaunay, Amalia; Méndez, César (Frontiers in Earth Science, 2022)
Deglaciation modelling of the Patagonian Ice Field since the Last Glacial Maximum has been a topic of intensive research in Central West Patagonia (44°-49°S). However, the chronology of deglaciation onset, its acceleration and the subsequent thinning and recession of the different ice lobes as well as the timing and extension of large pro-glacial systems are still a matter of discussion. Particularly, the Lago Cochrane/Pueyrredón Ice Lobe reached its eastward maximum extension around ~20, 000-27,000 cal yrs BP and its associated pro-glacial lake drained to towards the Pacific at a time between 13,000 and 8,000 cal yrs BP. This research presents the first two pollen and charcoal records from the Lago Cochrane/Pueyrredón valley spanning the last 11,500 cal yrs BP. The Laguna Maldonado record spans between 11,700 and 7700 cal yr BP, while the Laguna Anónima records the last 8500 cal yr BP, thereby chronologically overlapping. The lithological record of Laguna Maldonado shows that the organic sedimentation began at the onset of the Holocene (11,700 cal yr BP), once the site was free of glacio-lacustrine influence. Between 11,650 and 10,500 cal yrs BP, an open Nothofagus forest developed associated with a high fire occurrence frequency followed by a transitional phase to a closer forest associated to fire regime shift to a low fire activity up to 9,800 cal yrs BP. Between 9,800-8000 cal yrs BP the Laguna Maldonado record suggests the development of an open forest or probably scattered patches of forest of variable size into a steppe matrix, probably related to geomorphological and volcanic rather than climatic forcings while the Laguna Anónima record points out the development of a close Nothofagus forest and low fire occurrence frequency from 8500 to 3800 cal yrs BP. From 3800 cal yrs BP a highly dynamic open forest or forest patches scattered in a grass/ shrub-grass steppe matrix occurred around Laguna Anónima associated with a high fire occurrence frequency synchronous with an important human demographic increase in the last 3000 years. The results from the Lago Cochrane/Pueyrredón valley are integrated and discussed at the regional scale with other records from Central West Patagonia.